2010
DOI: 10.1136/adc.2009.181701
|View full text |Cite
|
Sign up to set email alerts
|

Maternal methadone therapy increases QTc interval in newborn infants

Abstract: Maternal methadone therapy can cause transient prolongation of the QTc interval in newborn infants in the first 2 days of life. Newborns exposed to methadone are at risk of cardiac rhythm disturbances. Bradycardia, tachycardia or an irregular heart rate in an infant born to a mother on methadone treatment should prompt investigation with a 12-lead ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Even though methadone reduces symptoms compared with illicit opiate use, clinical cohorts have demonstrated that prenatal methadone exposure can lead to increased premature birth (Cleary et al, 2012;FajemirokunOdudeyi et al, 2006;Lejeune et al, 2006), decreased birthweight (Cleary et al, 2012;Hulse et al, 1997;Kandall et al, 1976;Sarfi et al, 2009;, and smaller head circumference (Brown et al, 1998;Hans, 1989;Rosen and Johnson, 1985;Welle-Strand et al, 2013;Wilson et al, 1981). Additional reports indicate an increased incidence of respiratory insufficiency at birth (Maas et al, 1990), altered corrected QT interval on electrocardiogram during the first postnatal week (Parikh et al, 2011), postnatal hyperphagia (Martinez et al, 1999), disrupted auditory event related potentials (Paul et al, 2014), and myelination deficits (Walhovd et al, 2012). However, the prevalence of cognitive impairments produced by prenatal methadone has been questioned because some studies have not observed differences in cognitive development (de Cubas and Field, 1993;Hans, 1989;Rosen and Johnson, 1985) or performance (Bauman and Levine, 1986;Soepatmi, 1994;van Baar, 1990;van Baar and de Graaff, 1994;.…”
Section: Methadonementioning
confidence: 99%
“…Even though methadone reduces symptoms compared with illicit opiate use, clinical cohorts have demonstrated that prenatal methadone exposure can lead to increased premature birth (Cleary et al, 2012;FajemirokunOdudeyi et al, 2006;Lejeune et al, 2006), decreased birthweight (Cleary et al, 2012;Hulse et al, 1997;Kandall et al, 1976;Sarfi et al, 2009;, and smaller head circumference (Brown et al, 1998;Hans, 1989;Rosen and Johnson, 1985;Welle-Strand et al, 2013;Wilson et al, 1981). Additional reports indicate an increased incidence of respiratory insufficiency at birth (Maas et al, 1990), altered corrected QT interval on electrocardiogram during the first postnatal week (Parikh et al, 2011), postnatal hyperphagia (Martinez et al, 1999), disrupted auditory event related potentials (Paul et al, 2014), and myelination deficits (Walhovd et al, 2012). However, the prevalence of cognitive impairments produced by prenatal methadone has been questioned because some studies have not observed differences in cognitive development (de Cubas and Field, 1993;Hans, 1989;Rosen and Johnson, 1985) or performance (Bauman and Levine, 1986;Soepatmi, 1994;van Baar, 1990;van Baar and de Graaff, 1994;.…”
Section: Methadonementioning
confidence: 99%
“…(35, 36, 7881) These women have high rates of co-occurring mental health disorders – mood disorders, anxiety, and post-traumatic stress disorder,(82) as well as histories of physical and sexual abuse. (83) Polydrug use is common and the impact of other potential drug-drug interactions on the fetus are poorly understood.…”
Section: Prenatal Carementioning
confidence: 99%
“…Among reports of 27 newborns with in utero exposure to methadone, 1 developed bradycardia and 4 transiently developed QTc intervals greater than 460 msec. 5,6 In a study of intravenous methadone in 7 neonates between 33 and 45 weeks postmenstrual age, the maximum QTc interval prolongation was 10.4 msec; however, all QTc intervals remained within the normal range. 12 In 2 pediatric patients (ages 11 and 17 years) receiving methadone for chronic pain, 1 had no change in QTc interval and the other had QTc prolongation in the setting of concomitant QTc-prolonging drugs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Existing evaluations of the QTc-prolonging effects of methadone in children are limited to very small studies and case reports (73 total children) that reach varying conclusions regarding the degree of QTc prolongation induced by methadone. [4][5][6][7][8] Notably, existing studies have largely excluded critically ill children, including those with underlying cardiac disease. Critically ill children are among the most frequent recipients of methadone therapy.…”
Section: Introductionmentioning
confidence: 99%